A concise guide to sustainable PEMFCs: recent advances in improving both oxygen reduction catalysts and proton exchange membranes. (21st August 2015) - Scofield, Megan E.; Liu, Haiqing; Wong, Stanislaus S.
<x xml:space="preserve">Abstract</x> The rising interest in fuel cell vehicle (FCV) technology has created a growing and timely need and realization to develop rational chemical strategies to create highly efficient, durable, and cost-effective fuel cells.